A primeira vista: uma análise sobre a identidade e a representação das mulheres negras da página “Profissionais Negros do Ceará” no Instagram - Silva, Luizete Vicente da (2023)
This thesis aims to offer reflections about the identity and representation of the black population and especially of black women on Profissionais Negros do Ceará page, on Instagram. The research carries out a gender and race clipping which tries to understand how this web page crosses texts and images, with other platform tools such as likes, comments and shares. We also have the application of the semi-structured interview model that allowed us to establish a dialogue with the interviewees. In this qualitative research, we have as methodological inspiration the multisituated ethnography, to observe how the construction of this digital mosaic of identities and their representations occurs. In addition to observing the functionality of hashtags, keyword, icons and other tools which provide the indexing of topics and/or discussions on the social network.